Upgrading to 5G Networks: Existing Challenges and Potential Solutions - Alnaas, M; Laias, E; Hanasih, A; Alhodairy, O (International Journal of Computer Sciences and Engineering, 2023)
The introduction of t The fifth generation (5G) networks indeed brings significant advancements in connectivity and has the potential to revolutionize various industries. The technologies that make 5G powerful include features such as faster speeds, reduced latency, increased capacity, and the ability to connect a wide range of devices and objects. However, implementing 5G networks involves upgrading existing infrastructure and deploying new infrastructure, which can be both costly and time-consuming. This process requires significant investments from telecommunication companies to install new equipment and upgrade existing infrastructure to support 5G technology. Additionally, the deployment of 5G networks requires a substantial amount of radio spectrum, and regulatory frameworks need to be in place to allocate and manage the spectrum effectively. This paper provides an overview of 5G technologies, highlighting their key features and potential benefits. It also delves into the existing challenges that arise with the implementation of 5G networks and discusses some possible solutions to address these challenges.